Books through bars: stories from the prison books movement - Marquis, Moira; Marquis, Dave "Mac" (University of Georgia Press, 2024)
"Co-edited by two activists with deep experience in organizing prison books programs (PBPs), Books Behind Bars introduces readers to PBPs and their decentralized organization. PBPs are a grassroots-level and nationwide activist movement challenging the largest prison industry in the world by refusing to let incarcerated people remain isolated and forgotten. Operating on shoestring budgets, will all-volunteer workforces and donated libraries, books to prisoner programs are examples of ordinary people acting to undermine the isolation and judgment of incarceration. Although there are currently fifty-three books to prisoners groups serving in all fifty states, these programs remain relatively unknown. The goal of this book is to bring awareness to this diffuse and long-standing social movement and offer readers a way to get involved. In addition to highlighting voices from PBPs throughout the United States, the volume also includes essays, images, and artwork from independent bookstore owners, formerly and currently incarcerated folks, activists, artists, journalists, volunteers, organizers, and scholars"--